Analysis of the Business Position of PT MHE Demag Indonesia Makassar Branch Using the Typology Miles and Snow Strategy - Lufthansa Ardian; Abdul Rahman Kadir; Abdullah Sanusi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to identify the business position of PT MHE Demag Indonesia in the Makassar Branch. This research is designed to direct the strategic decisions of the new branch in Makassar. The managerial strategy decisions in this study are in the scope of GE (general electric) analysis and Miles & Snow typology analysis. Location or place of research in Makassar, Sulawesi. The data collected includes secondary data. The population and sample in this study include general managers, managers, and assistant managers to the board of directors totaling 30 people. Data analysis techniques using SWOT analysis, TOWS, BCG, General Electric, and Miles & Snow. The results showed that the business of PT MHE Demag Indonesia in the Makassar branch was generally in a profitable position with sufficient potential resources. Efforts to increase the competitive advantage of Branch Offices by maximizing all the strengths and opportunities they have, while simultaneously minimizing weaknesses and threats. Based on the analysis of Miles and Snow used, based on the People and Marketing indicators, the Makassar Branch implements the Prospector strategy, the customer care, and products indicators apply the analyzers strategy, while the process and financial indicators apply the defender strategy.